CHANGES IN DEFORMATION WITHIN CARBONIFEROUS MASS TRANSPORT DEPOSITS, AGUA DE LA PEÑA CREEK (SAN JUAN, ARGENTINA) - (:unkn) unknown (My University, 2025)
ABSTRACT Mass transport deposits (MTDs) play a critical role in sediment reworking and distribution within marine environments. Agua de la Peña Creek (San Juan Province, Argentina) provides a well-exposed Carboniferous succession that records the final stages of the Late Paleozoic Ice Age (LPIA) along the western margin of Gondwana. This succession, up to 1000 meters thick, consists of proglacial to subglacial sediment ranging from distal turbidites and shales to MTDs containing exotic clasts. Previous studies have primarily focused on the general characteristics and deformation of these deposits. By pairing stratigraphic sections with high-resolution imagery, this study aims to provide a detailed assessment of a singular flow evolution across a 300-meter outcrop, improving an understanding of mass transport process within proglacial to post-glacial environments along this section of western Gondwana. The study integrates deformation analysis, sediment body geometry, and high-resolution imagery to assess a singular mass transport at multiple scales. Findings indicate that (1) the basal shear zone of the studied MTD exhibits a transitional domain between erosion and liquefaction; (2) vertical deformation patterns in the MTD show a progressive increase in mixing and homogenization intensity from the base upward, with localized zones of complex deformation and kinematic indicators; (3) laterally in the MTD, block abundance and deformation varies broadly across an oblique cut to the overall direction of flow, which is likely due to lobe deflection, energy dissipation through unconfined flow distribution, and/or the total distance from the headwall scarp; (4) there is no evidence of glacial proximal-distal influence within the studied deposit. These results refine models of basal deformation, as well as vertical and lateral variability. Furthermore, they offer a comparative framework for evaluating deformation patterns in other depositional settings within ancient deposits.
Keywords: Sedimentary geology; Mass transport; Sediment gravity flows; Slope Failure; Slumps; Turbidites